A new highly effective hybrid fungicide containing difenoconazole and tea tree oil for managing scab of apple, pecan and almond trees and as a tool in resistance management. (23rd July 2022) - Reuveni, Moshe; Gur, Lior; Henriquez, José Luis; Frank, James; Tedford, Eric; Cloud, Gary; Adaskaveg, James E.
Abstract: Management of scab diseases of apple, pecan and almond is mostly based on fungicide applications according to host phenological stage and wetness events. Resistance to widely used locally systemic fungicides including the methyl benzimidazoles, demethylation inhibitors (DMIs) and quinone outside inhibitors (QoIs) has been reported. We evaluated the activity of a new premixed hybrid fungicide containing the DMI difenoconazole and essential tea tree oil (TTO) against mycelial growth of Venturia inaequalis in vitro and against scab of apple, pecan and almond in field trials. Mycelial growth of 24 isolates of V . inaequalis collected from commercial apple orchards varied in their sensitivity to difenoconazole (EC50 values of 0.0002–1.29 mg/L). Difenoconazole–TTO was significantly more inhibitory to some of the isolates than difenoconazole alone, primarily to those that were less sensitive to difenoconazole. Protective foliar applications of difenoconazole–TTO in field trials were highly effective in controlling scab of apple and generally provided significantly higher disease control than difenoconazole alone. On apple and almond, difenoconazole–TTO treatments were similarly or more effective than applications with other synthetic fungicides belonging to the DMI, QoI and succinate dehydrogenase inhibitor (SDHI) groups, or their mixtures. Difenoconazole–TTO completely prevented scab on pecan trees. Results suggest that difenoconazole–TTO can be integrated into scab control programmes for these crops and be used as a strategic approach in fungicide resistance management in orchards. Abstract : The hybrid difenoconazole–TTO fungicide is highly effective against apple, pecan and almond scab. It can be integrated into scab control programmes and be used as a strategic approach to fungicide resistance management in orchards.